"I Need That Week Off!": An Experiential Exercise on Conflict and Negotiation. (3rd July 2017) - Robinson, Melanie A.
ABSTRACT: This article presents an experiential exercise designed to provide students with an opportunity to develop their knowledge of ways in which conflict may be managed (using the framework proposed by Thomas, 1976) and types of negotiation. Students form pairs and are presented with a scenario in which they have both requested the same week of vacation to attend events. Unfortunately, they are informed that they are unable to take the time off simultaneously. Participants are asked to discuss among themselves, using assigned modes of managing conflict, to determine how the time will be allocated. The target audience is composed of undergraduate students, who may be enrolled in any number of classes related to organizational behavior. To examine perceptions of the exercise, data were collected from a sample of 140 participants. Among the findings, 92.9% of respondents reported that they would recommend that instructors use the exercise in a similar course.